Ciliary phenotyping in renal epithelial cells in a cranioectodermal dysplasia patient with WDR35 variants - Walczak-Sztulpa, Joanna; Wawrocka, Anna; Kuszel, Łukasz; Pietras, Paulina; Leśniczak-Staszak, Marta; Andrusiewicz, Mirosław; Krawczyński, Maciej R.; Latos-Bieleńska, Anna; Pawlak, Marta; Grenda, Ryszard; Materna-Kiryluk, Anna; Oud, Machteld M.; et al. (Frontiers in Molecular Biosciences, 2023)
Background: Cranioectodermal dysplasia (CED) is a skeletal autosomal recessive ciliopathy. The characteristic clinical features of CED are facial dysmorphisms, short limbs, narrow thorax, brachydactyly, ectodermal abnormalities and renal insufficiency. Thus far, variants in six genes are known to be associated with this disorder: WDR35, IFT122, IFT140, IFT144, IFT52, and IFT43. Objective: The goal of this study was to perform cilium phenotyping in human urine-derived renal epithelial cells (hURECs) from a CED patient diagnosed with 2nd stage chronic kidney disease (CDK) and three unrelated and unaffected pediatric controls. Methods: Genetic analysis by WDR35 screening was performed in the affected individual. Cilium frequency and morphology, including cilium length, height, and width, were evaluated by immunofluorescence (IF) experiments in hURECs using two markers visualizing the ciliary axoneme (Acte Tub and ARL13B) and the base of the cilium (PCNT). The IF results were analyzed with a confocal microscope using IMARIS software. Results: WDR35 analysis revealed the presence of a known nonsense p.(Leu641*) variant and a novel missense variant p.(Ala1027Thr). Moreover, CGH analysis showed that the patient carries a microdeletion on chromosome 7q31.1. Ciliary phenotyping performed on hURECs showed morphological differences in the patient’s cilia as compared to three controls. Cilia of the CED patient were significantly wider and longer. Conclusion: The obtained results suggest that CED-related 2nd stage CKD might be associated with cilia abnormalities as identified in renal epithelial cells from a CED patient harboring variants in WDR35. This study points out the added value of hURECs in functional testing for ciliopathies.